Antibiotic removal does not affect cecal microbiota balance and productive parameters in LP robust rabbit line - Montoro-Dasi, Laura; Lorenzo-Rebenaque, Laura; Ramon-Moragues, Adrian; Pérez-Gracia, Maria Teresa; de Toro, María; Marin, Clara; Villagra, Arantxa (Frontiers in Veterinary Science, 2022)
Antimicrobial resistance is an important threat to public health worldwide, being one of the main death causes in 2050. Moreover, global health is currently underpinned by the ‘One Health’ concept, whereby livestock is strictly related to human and environmental health. However, in the case of the meat rabbit industry, antibiotic additives are still added to prevent gastrointestinal diseases. Current food and consumer awareness require the implementation of sustainable production systems, where robustness and resilience are increasingly important. Hence, the aim of this study was to evaluate the effect of antibiotic feed supplementation on microbiota, and productive performance during the rabbit growing period in a robust genetic line. For this purpose, a total of 432 weaned rabbits were randomly housed, cecum samples were taken on the weaning day and at the end of the growing period (28 and 61 days of age, respectively), and 16S rRNA sequencing analysis was performed. Results showed a higher microbiota complexity at the end of growing in both experimental groups. Firmicutes represented the dominant phylum of the cecal community, followed by Bacteroidota in both groups. Moreover, Victivallis and Escherichia-Shigella genera were only identified in the experimental group without antibiotic supplementation at the end of the growing period. In conclusion, antibiotic feed supplementation had no effect on microbiota composition and productive performance in the robust genetic line reared. These results evidence the importance of the development of rabbit robust genetic lines as an alternative tool to antibiotic administration in epizootic enteropathy control.